Diagnostic performance of apparent diffusion coefficient values in differentiating benign from malignant lesions in prostate PI-RADS v2.1 category 1 "nodules in nodule". - Sun, Minghua; Li, Fei; Zhang, Xiaoyan; Wu, Rui; Liu, Wenya; Xu, Li; Wu, Mengjie; Wang, Yangang (Abdominal Radiology, 2025)
Objectives: To explore the associations between the apparent diffusion coefficient (ADC) values of prostate PI-RADS v2.1 category 1 "nodules in nodule" and their pathological characteristics. Methods: We retrospectively analyzed the prostate images from 226 male patients who underwent biopsy following MRI from January 2019 to December 2024. Two radiologists evaluated the PI-RADS v2.1 categories of identified nodules, measured the ADC values of the prostate nodules in a double-blind manner, and analyzed the associations between these values and the pathological characteristics of the nodules via independent sample t tests or Mann-Whitney U test. Results: The ADC values of PI-RADS v2.1 category 1 "nodules in nodule" pathologically confirmed as clinically significant prostate cancer (csPCa) were lower than those of benign prostate hyperplasia (BPH) ((unit in ×10− 3 mm2/s)TZ: 0.739 ± 0.15 versus 0.984 ± 0.24; PZ: 0.719 ± 0.17 versus 1.036 ± 0.21, p < 0.001). The AUCs were 0.799 (TZ) with a cutoff of 0.835 × 10− 3mm2/s, and 0.873(PZ) with a cutoff of 0.795 × 10− 3mm2/s, respectively. The total prostate-specific antigen (tPSA), free/t PSA, PSA density (PSAD), and prostate gland volume (PGV) differed significantly between patients with PI-RADS v2.1 "nodules in nodule" that were pathologically confirmed as csPCa and patients with BPH (all p < 0.05). Conclusion: In patients with PI-RADS v2.1 category 1 "nodules in nodule", when the ADC values are less than 0.835 × 10− 3mm2/s in the TZ, the PI-RADS v2.1 score of the nodule can be upgraded to 3.